Luminescent properties of Na2GdMg2(VO4)3:Eu3+ red phosphors for NUV excited pc-WLEDs. Issue 9 (1st May 2021) - Tong, Ye; Chen, YiHang; Chen, SunYueZi; Wei, RongFei; Chen, LiPing; Guo, Hai
Abstract: Herein, a series of novel Na2 GdMg2 (VO4 )3 :Eu 3+ (NGMVO:Eu 3+ ) red phosphors were elaborated by conventional solid-state reaction process. Their structural features, luminescent properties, energy transfer were researched at length. XRD patterns indicate that NGMVO:Eu 3+ crystallized in single cubic garnet structure. Under the excitation of near ultraviolet light at 356 nm, the emission spectra of NGMVO host could be divided in two parts that resulted from 3 T2 → 1 A1 and 3 T1 → 1 A1 transitions of VO4 3− . While NGMVO:Eu 3+ phosphors show intense sharp red emission peaks including 590, 610, 652 and 706 nm that originated from 5 D0 → 7 FJ (J = 1–4) transitions of Eu 3+, respectively. The optimal concentration of Eu 3+ is 0.7. Importantly, NGMVO:0.7Eu 3+ sample presents high energy transfer efficiency (89 %) and high external quantum efficiency (48.3 %). Besides, its emission intensity remains 79 % at 420 K compared with that at 300 K, proving the good thermal stability of phosphors. All above results suggest that NGMVO:Eu 3+ red phosphors have latent applications in white light emitting diodes.